Hyperlipidemia in patients newly treated with anticonvulsants: A population study. (7th January 2020) - Mintzer, Scott; Yi, Misung; Hegarty, Sarah; Maio, Vittorio; Keith, Scott
Abstract: Objective: To determine the incidence of hyperlipidemia after first anticonvulsant treatment for seizures, using a large US administrative claims database. Methods: We obtained data from the MarketScan Commercial and Medicare databases for 2005‐2009 for all adult patients newly treated with an anticonvulsant for seizures who had no previous history of hyperlipidemia or treatment with a lipid‐lowering agent. We divided the population based upon whether they were treated with an enzyme‐inducing anticonvulsant (phenytoin, carbamazepine, phenobarbital, primidone) or a noninducing anticonvulsant (all others). The primary outcome measure was a new diagnosis of hyperlipidemia during subsequent follow‐up. We accounted for a large number of demographic and clinical covariates. Results: Of 11 374 subjects, 8778 (77%) were prescribed noninducers and 2596 (23%) were prescribed inducers. New hyperlipidemia diagnoses were seen in 14.6% of the patients started on inducing anticonvulsants and 10.7% of the patients started on noninducing anticonvulsants ( P  < .001). Both hyperlipidemia and the use of inducers were significantly associated with older age and male gender. After accounting for covariates, inducer prescription was still associated with 23% higher odds of a subsequent diagnosis of hyperlipidemia (odds ratio = 1.225, 95% confidence interval = 1.066‐1.408, P  < .001). Significance: The use of enzyme‐inducing anticonvulsants in patients with newly diagnosed epilepsy was associated with a significant increase in subsequent diagnoses of hyperlipidemia, suggesting that the lipid‐elevating properties of these agents are of genuine clinical importance. This adds to the body of data demonstrating that these agents are likely associated with additional hassle, cost, and morbidity.